Resin sheet, laminated board, metal-clad laminated board, printed wiring board, and semiconductor package

By adding a specific proportion of number average molecular weight high elastomer and inorganic filler material to the resin sheet, the problem of easy breakage and poor thermal expansion in the resin sheet in the state without support is solved, and excellent dielectric characteristics in the high frequency band are achieved. Industrial shipping, suitable for high-frequency electronic equipment.

CN119173561APending Publication Date: 2024-12-20RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480002369.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-19
Filing Date
2024-04-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing resin sheet is difficult to handle without a support, is easy to break and has poor thermal expansion, and cannot meet the dielectric characteristics requirements in the high frequency band, especially the requirements for relative dielectric constant and dielectric loss tangent above the 10GHz frequency band. Within range.

Method used

Developed a resin sheet containing an elastomer with a number average molecular weight of 10,000 or more and an inorganic filler material, with a component ratio of 25% to 70% by volume, and a fracture energy of 0.1mJ/mm3 or more, which can be adsorbed and transported on a vacuum adsorption pad It is kept intact and has low thermal expansion, with a dielectric constant between 2.50 and 3.30, and a dielectric loss tangent below 0.0020.

Benefits of technology

The durability and low thermal expansion of resin sheets transported by vacuum adsorption pads on industrial scale are achieved, and the high-frequency band dielectric characteristics requirements are met above the 10GHz frequency band, and are suitable for the manufacture of laminated plates, printed circuit boards and semiconductor packages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107455550000111
    Figure BDA0005107455550000111
  • Figure BDA0005107455550000112
    Figure BDA0005107455550000112
  • Figure BDA0005107455550000121
    Figure BDA0005107455550000121
Patent Text Reader

Abstract

Provided is a resin sheet which can withstand adsorption and transport by means of a vacuum adsorption pad for transport, has low thermal expansion properties, and has a relative dielectric constant (Dk) of 2.50-3.30 in a high-frequency band of 10 GHz or more and a dielectric loss tangent (Df) of 0.0020 or less in a high-frequency band of 10 GHz or more. Also provided are a laminated board, a printed wiring board, and a semiconductor package, each of which is manufactured using the resin sheet. Specifically, the resin sheet contains (A) a resin component and (B) an inorganic filler, the component (A) contains (A1) an elastomer having a number average molecular weight of 10,000 or more, the content of the component (B) is 25-70 vol% based on the total amount of the resin sheet, and the breaking energy of the resin sheet is 0.1 mJ / mm3 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a resin sheet, a laminate, a metal-clad laminate, a printed wiring board, and a semiconductor package. Background Art

[0002] The signals used in mobile communication devices such as mobile phones, their base station equipment, servers, routers and other network infrastructure equipment, large computers, etc. are becoming faster and larger year by year. Along with this, the printed circuit boards carried by these electronic devices need to cope with high frequencies, requiring substrate materials with excellent dielectric properties in high frequency bands, that is, small relative dielectric constant (Dk) and dielectric loss tangent (Df), which can reduce transmission losses.

[0003] On the other hand, with the miniaturization of electronic equipment, the high-density installation of electronic components used in printed circuit boards is also being promoted. In order to achieve this high-density installation, PGA (Pin Grid Array) type packages have been used. The PGA type package has the following structure: the pins protrude from the back of the substrate in a grid-like manner at a certain interval in the vertical direction. The size of the pins and the intervals between the pins are usually fixed, and it is difficult to change its design in most cases. If the relative dielectric constant of the substrate material is reduced, it is necessary to reduce the pins of the PGA type package and reduce the intervals between the pins, but as mentioned above, since it is difficult to make this design change, the relative dielectric constant of the substrate material needs to be maintained at the desired value in advance. That is, in order to achieve high-frequency response while achieving high-density installation, it is necessary to reduce the dielectric loss tangent while maintaining the relative dielectric constant of the substrate material at the desired value. For material manufacturers, it is urgent to develop such a substrate material.

[0004] So far, as a substrate material capable of achieving low transmission loss, a prepreg using a thermosetting resin composition having excellent dielectric properties in a high frequency band has been developed (for example, see Patent Document 1). The prepreg is formed from an aggregate and a thermosetting resin composition, and due to the presence of the aggregate, the prepreg can be processed without a support.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-169276 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, glass cloth, which is one of the representatives of aggregate, is made by bundling and weaving a plurality of glass fibers into twisted glass strands in the presence of a sizing agent, and usually contains impurities (B2O3, CaO, MgO, Na2O, etc.) from glass components other than SiO2 and impurities such as the sizing agent. According to the research of the inventors, it has been found that since the impurities deteriorate the dielectric properties, there are limitations in responding to the high improvement requirements related to the dielectric loss tangent (Df) today. Therefore, in the existing prepreg, the situation of making a simple resin sheet without using glass cloth has been studied. Since there is no aggregate, if it is not in the state of a support such as a polyethylene terephthalate (PET) film, the problem of the resin sheet being broken or destroyed into powder will occur, and at the same time, the low thermal expansion is also damaged.

[0010] In this case, in order to provide a resin sheet that can be processed even in a non-supported state, has low thermal expansion and has a relative dielectric constant (Dk) and dielectric loss tangent (Df) within a specified range in a high frequency band above 10 GHz, the applicant has filed an international patent application (PCT / JP2021 / 038025) for the following resin sheet: "A resin sheet comprising (A) a resin component and (B) an inorganic filler, wherein the (A) component contains (A1) an elastomer having a number average molecular weight of more than 10,000, and the content of the (A1) component is more than 30% by mass based on the (A) component, and the content of the (B) component is 40 to 95% by volume based on the total amount of the resin sheet."

[0011] However, the inventors conducted further research and found that the resin sheet described in the above-mentioned international patent application (PCT / JP2021 / 038025) can indeed be processed in a state without a support body (having self-supporting properties (Japanese: self-sustaining)) and can be transported manually, but if a method of transporting the resin sheet by adsorbing it with a vacuum adsorption pad is adopted for implementation on an industrial scale, the resin sheet tends to break easily.

[0012] In view of the above, the purpose of the present application is to provide a resin sheet that can withstand adsorption and transportation using a vacuum adsorption pad for transportation, has low thermal expansion, and has a relative dielectric constant (Dk) of 2.50 to 3.30 in a high frequency band above 10 GHz and a dielectric loss tangent (Df) of 0.0020 or less in a high frequency band above 10 GHz. Furthermore, the purpose of the present application is to provide a laminated board, a printed wiring board, and a semiconductor package manufactured using the resin sheet.

[0013] Means for solving problems

[0014] The present inventors have conducted studies to achieve the above-mentioned object, and as a result, have found that the object can be achieved by the present application.

[0015] The present application includes the following embodiments [1] to

[13] .

[0016] [1] A resin sheet comprising (A) a resin component and (B) an inorganic filler, wherein:

[0017] The component (A) contains (A1) an elastomer having a number average molecular weight of 10,000 or more,

[0018] The content of the component (B) is 25 volume % to 70 volume % based on the total amount of the resin sheet.

[0019] The fracture energy of the resin sheet is 0.1 mJ / mm 3 above.

[0020] [2] The resin sheet according to [1], wherein

[0021] The component (A1) contains one or more selected from styrene elastomers, maleimide elastomers, olefin elastomers, urethane elastomers, polyester elastomers, polyamide elastomers, acrylic elastomers, silicone elastomers and derivatives thereof.

[0022] [3] The resin sheet according to [1] or [2], further comprising (A2) an elastomer having a number average molecular weight of less than 10,000.

[0023] [4] The resin sheet according to any one of [1] to [3], wherein

[0024] The component (A) further contains (A3) a thermosetting resin.

[0025] [5] The resin sheet according to [4], wherein

[0026] The component (A3) contains one or more selected from epoxy resins, phenolic resins, unsaturated imide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, vinylbenzyl resins, dicyclopentadiene resins, silicone resins, triazine resins, modified polyphenylene ether resins and melamine resins.

[0027] [6] The resin sheet according to [4] or [5], wherein

[0028] The total content of the component (A1) and the component (A2) is 40% by mass to 95% by mass based on the component (A).

[0029] [7] The resin sheet according to any one of [1] to [6], which does not contain an organic solvent, or even if it contains an organic solvent, the content of the organic solvent is less than 1% by mass based on the total amount of the resin sheet.

[0030] [8] The resin sheet according to any one of [1] to [7], which does not contain glass fibers, or even if it contains glass fibers, the content of the glass fibers is 10% by volume or less based on the total amount of the resin sheet.

[0031] [9] The resin sheet according to any one of [1] to [8], wherein

[0032] When adsorbed by a silicone vacuum pad with a diameter of 20 mm, the vacuum degree at break is -15 kPa or less.

[0033]

[10] A laminated plate comprising a cured product of the resin sheet according to any one of [1] to [9].

[0034]

[11] A metal-clad laminate comprising a metal foil and a cured product of the resin sheet according to any one of [1] to [9].

[0035]

[12] A printed wiring board comprising the laminate according to

[10] or the metal-clad laminate according to

[11] .

[0036]

[13] A semiconductor package comprising the printed wiring board according to

[12] and a semiconductor element.

[0037] Effects of the Invention

[0038] According to the present application, a resin sheet can be provided: the resin sheet can withstand adsorption and transportation by a vacuum adsorption pad for transportation, has low thermal expansion, has a relative dielectric constant (Dk) of 2.50 to 3.30 in a high frequency band above 10 GHz, and has a dielectric loss tangent (Df) of 0.0020 or less in a high frequency band above 10 GHz. Furthermore, a laminate, a printed wiring board, and a semiconductor package manufactured using the resin sheet can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a picture showing the state of the resin sheet when a break occurs in the adsorption portion of the resin sheet during the measurement of the breaking vacuum degree. DETAILED DESCRIPTION

[0040] In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may also be replaced by the values ​​shown in the embodiments. In addition, the lower limit and upper limit of the numerical range may be arbitrarily combined with the lower limit or upper limit of other numerical ranges. In the representation of the numerical range "AA to BB", the numerical values ​​AA and BB at both ends are included in the numerical range as the lower limit and upper limit, respectively.

[0041] In this specification, for example, the description "10 or more" means 10 and values ​​exceeding 10, and this also applies when the values ​​are different. In addition, for example, the description "10 or less" means 10 and values ​​less than 10, and this also applies when the values ​​are different.

[0042] In addition, each component and material exemplified in this specification may be used alone or in combination of two or more unless otherwise specified. In this specification, when there are multiple substances belonging to each component in the composition, the content of each component in the composition means the total amount of the multiple substances present in the composition unless otherwise specified.

[0043] In this specification, the "solid content" refers to non-volatile components other than water and a diluent described below contained in the photosensitive resin composition, and also includes components that are liquid, paste-like, and waxy at room temperature around 25°C.

[0044] In this specification, "relative dielectric constant" and "dielectric loss tangent" refer to "relative dielectric constant" and "dielectric loss tangent" in the 10 GHz band even if not otherwise specified. In this specification, relative dielectric constant and dielectric loss tangent are sometimes collectively referred to as "dielectric properties".

[0045] Any combination of the matters described in this specification is also included in the present application and the present embodiment.

[0046] [Resin sheet]

[0047] One aspect of the present embodiment is the following resin sheet.

[0048] A resin sheet comprising (A) a resin component and (B) an inorganic filler, wherein:

[0049] The component (A) contains (A1) an elastomer having a number average molecular weight of 10,000 or more,

[0050] The content of the component (B) is 25 to 70% by volume based on the total amount of the resin sheet.

[0051] The fracture energy of the resin sheet is 0.1 mJ / mm 3 above.

[0052] Here, the expression "a resin sheet containing ..." includes two types of resin sheets: a resin sheet directly containing the components described in ... and a resin sheet obtained by reacting at least a part of the components described in ....

[0053] By setting the breaking energy of the resin sheet of the present embodiment to 0.1 mJ / mm 3 As described above, the resin sheet can withstand the suction and transportation by the vacuum suction pad for transportation (hereinafter, this property may be referred to as "industrial transportability"). From the same viewpoint, the fracture energy of the resin sheet is preferably 0.5 mJ / mm 3 More preferably, 1.0 mJ / mm 3 More preferably, 1.5 mJ / mm 3 It should be noted that the fracture energy of the resin sheet is 1.0 mJ / mm 3 In the above case, there is a tendency that the work of peeling the resin sheet from the support such as PET can be performed by machine (automation), which is preferable from the viewpoint of industrial implementation.

[0054] The upper limit of the breaking energy of the resin sheet of the present embodiment is not particularly limited, and may be 4.0 mJ / mm 3 Below, can be 3.5mJ / mm 3 Below, can be 3.0mJ / mm 3 Below, can be 2.8mJ / / mm 3 the following.

[0055] That is, the breaking energy of the resin sheet of the present embodiment can be 0.1 to 4.0 mJ / mm. 3 .

[0056] There is no particular limitation on the method for making the breaking energy of the resin sheet of the present embodiment fall within the above range, and examples thereof include: (i) a method of adjusting the content of the component (A1) within the range described below, (ii) a method of adjusting the content of the component (B) within the range described below, and a combination of (i) and (ii).

[0057] Although there are no special restrictions, from the viewpoint of easy implementation of adsorption and transportation using a vacuum adsorption pad for transportation, the vacuum degree at which the resin sheet of this embodiment breaks when adsorbed on a silicone vacuum adsorption pad with a diameter of 20 mm (adsorption portion shape: circular) (hereinafter sometimes referred to as the breaking vacuum degree) is preferably below -15 kPa, more preferably below -20 kPa, further preferably below -30 kPa, and particularly preferably below -40 kPa. Although there are no special restrictions, the vacuum degree can be above -150 kPa, above -120 kPa, or above -100 kPa.

[0058] A more detailed method for measuring the fracture vacuum is described in the examples.

[0059] The resin sheet of this embodiment can withstand adsorption and transportation using a vacuum adsorption pad for transportation, has low thermal expansion, a relative dielectric constant (Dk) of 2.50 to 3.30 in the high frequency band above 10 GHz, and a dielectric loss tangent (Df) of less than 0.0020 in the high frequency band above 10 GHz.

[0060] The relative dielectric constant (Dk) is preferably 2.65 to 3.30, more preferably 2.70 to 3.20, further preferably 2.75 to 3.10, and particularly preferably 2.80 to 3.10.

[0061] The dielectric loss tangent (Df) is preferably 0.0018 or less, more preferably 0.0015 or less, further preferably 0.0010 or less, particularly preferably 0.0009 or less, and most preferably 0.0008 or less. The lower limit of the dielectric loss tangent (Df) is not particularly limited, and may be 0.0003 or more, 0.0004 or more, or 0.0005 or more.

[0062] It should be noted that the relative dielectric constant (Dk) and the dielectric loss tangent (Df) are values ​​measured using a separated dielectric resonator (SPDR), and more specifically, are values ​​measured according to the method described in Examples.

[0063] Furthermore, in a preferred embodiment of the resin sheet of the present embodiment, the resin sheet does not contain an organic solvent, or even if it contains an organic solvent, the content of the organic solvent is less than 1% by mass based on the total amount of the resin sheet. Nevertheless, since the resin sheet has sufficient flexibility, cracks are unlikely to occur, and the handling property is excellent. In a preferred embodiment of the resin sheet of the present embodiment, since the content of the organic solvent is small, there is an advantage that voids are less likely to occur during reflow soldering.

[0064] From the perspective of dielectric loss tangent (Df), in another preferred embodiment of the resin sheet of the present embodiment, the resin sheet does not contain glass fiber, or even if it contains glass fiber, the content of glass fiber is 10% by volume or less based on the total amount of the resin sheet (hereinafter, sometimes referred to as "feature A"), and despite this, its industrial transportability is excellent. In the case where the resin sheet contains glass fiber, from the perspective of dielectric loss tangent (Df), the content of glass fiber is preferably 7% by volume or less, more preferably 5% by volume or less, and further preferably 3% by volume or less based on the total amount of the resin sheet.

[0065] It should be noted that in the description text of feature A in one of the above-mentioned embodiments, the term "glass fiber" can also be replaced by "glass cloth" or "fiber substrate". That is, in another preferred embodiment of the resin sheet of the present embodiment, from the perspective of dielectric loss tangent (Df), the resin sheet does not include glass cloth, or even if it includes glass cloth, the content of glass cloth is 10% by volume or less based on the total amount of the resin sheet. In addition, in another preferred embodiment of the resin sheet of the present embodiment, from the perspective of dielectric loss tangent (Df), the resin sheet does not include a fiber substrate, or even if it includes a fiber substrate, the content of fiber substrate is 10% by volume or less based on the total amount of the resin sheet. In the case where the resin sheet of the present embodiment includes glass cloth or fiber substrate, their preferred content is the same as that of the above-mentioned glass fiber.

[0066] Hereinafter, each component contained in the resin sheet of this embodiment will be described in detail.

[0067] ((A) resin component, (A1) elastomer having a number average molecular weight of 10,000 or more)

[0068] The resin sheet of the present embodiment contains a resin component as the component (A), and the component (A) contains "(A1) an elastomer having a number average molecular weight of 10,000 or more".

[0069] The resin sheet of the present embodiment contains the component (A1), so that the resin sheet can be self-supporting even without a support and exhibits high flexibility. Furthermore, the resin sheet of the present embodiment contains the component (A1), so that it can have the predetermined relative dielectric constant (Dk) and dielectric loss tangent (Df).

[0070] From the viewpoint that the resin sheet can be self-supporting even without a support body, the number average molecular weight (Mn) of the component (A1) is preferably 15,000 or more, more preferably 18,000 or more, further preferably 25,000 or more, particularly preferably 35,000 or more, and most preferably 50,000 or more. The upper limit of the number average molecular weight of the component (A1) is not particularly limited, and from the viewpoint of circuit embeddability, it is preferably 300,000 or less, more preferably 250,000 or less, further preferably 200,000 or less, particularly preferably 120,000 or less, and most preferably 90,000 or less. That is, the number average molecular weight (Mn) of the component (A1) is preferably 10,000 or more and 300,000 or less.

[0071] In this specification, the number average molecular weight is a value determined by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent in terms of standard polystyrene.

[0072] Based on the component (A), the content of the component (A1) is preferably 20% by mass or more, i.e., 20 to 100% by mass, more preferably 25 to 90% by mass, further preferably 25 to 80% by mass, particularly preferably 30 to 70% by mass, and most preferably 35 to 65% by mass. By making the content of the component (A1) above the lower limit, the breaking energy of the resin sheet can be easily controlled to the specified value, thereby improving the industrial transportability of the resin sheet while having the specified relative dielectric constant (Dk) and dielectric loss tangent (Df).

[0073] (A1) component preferably contains one or more selected from styrene elastomer, maleimide elastomer, olefin elastomer, urethane elastomer, polyester elastomer, polyamide elastomer, acrylic elastomer, silicone elastomer and their derivatives. Although not particularly limited, among them, from the viewpoint of relative dielectric constant (Dk) and dielectric loss tangent (Df) with the regulation, preferably styrene elastomer, maleimide elastomer, more preferably styrene elastomer. Any elastomer can use commercially available products.

[0074] As the derivatives of the elastomer, there can be mentioned derivatives having reactive functional groups at the molecular ends or in the molecular chains of the elastomers. As the reactive functional groups, there can be mentioned acid anhydride groups, epoxy groups, hydroxyl groups, carboxyl groups, amino groups, amide groups, isocyanate groups, acrylic groups, methacrylic groups, vinyl groups, etc. The derivatives of the elastomer can have one reactive functional group or two or more. In addition, the reactive functional groups can be one or two or more.

[0075] (Styrene elastomer; component (A1))

[0076] The styrene-based elastomer is not particularly limited, and examples thereof include styrene-butadiene copolymers such as styrene-butadiene diblock copolymers and styrene-butadiene-styrene triblock copolymers; styrene-isoprene copolymers such as styrene-isoprene diblock copolymers and styrene-isoprene-styrene triblock copolymers; hydrogenated products of the styrene-butadiene copolymers; hydrogenated products of the styrene-isoprene copolymers, etc. These copolymers may or may not contain structural units derived from vinyl-containing aromatic compounds such as divinylbenzene.

[0077] The styrene-based elastomer may be used alone or in combination of two or more.

[0078] The number average molecular weight (Mn) of the styrene-based elastomer is the same as the number average molecular weight (Mn) of the component (A1).

[0079] The styrene content of the styrene elastomer is not particularly limited, but is preferably 10 to 70% by mass, more preferably 10 to 50% by mass, further preferably 10 to 40% by mass, and particularly preferably 15 to 35% by mass. Here, the styrene content refers to the content of the styrene structural unit relative to the total structural units. When the styrene content is above the lower limit, the heat resistance tends to be good, and when it is below the upper limit, the rubber elasticity tends to be excellent, and the industrial transportability and flexibility tend to be good.

[0080] The styrene elastomer may be unhydrogenated or a hydrogenated product. In the case of a hydrogenated product, the hydrogenation rate of the styrene elastomer is not particularly limited, but may be preferably 80 to 100 mol%, more preferably 85 to 100 mol%, further preferably 90 to 100 mol%, and may be 95 to 100 mol%.

[0081] As the styrene-based elastomer, commercially available products may be used, such as TAFTIC (registered trademark) H series, P series, and M series manufactured by Asahi Kasei Corporation, SEPTON (registered trademark) series manufactured by KURARAY Co., Ltd., and Kraton (registered trademark) G polymer series and D polymer series manufactured by Kraton Polymer Japan Co., Ltd.

[0082] (Maleimide elastomer; component (A1))

[0083] The maleimide elastomer is not particularly limited as long as it is an elastomer having a maleimide skeleton, and examples thereof include maleimide compounds having a structure in which a saturated or unsaturated aliphatic hydrocarbon group is bonded to a maleimide group, etc. The maleimide compound having a structure in which a saturated or unsaturated aliphatic hydrocarbon group is bonded to a maleimide group is preferably a maleimide compound having a structure in which a saturated or unsaturated aliphatic hydrocarbon group is bonded to a nitrogen atom of the maleimide group.

[0084] The maleimide compound having a structure in which a saturated or unsaturated aliphatic hydrocarbon group is bonded to a maleimide group is preferably a maleimide compound having at least two maleimide groups, more preferably a maleimide compound having a structure represented by one or more of the following general formula (1), and still more preferably a maleimide compound represented by the following general formula (2).

[0085] In addition, the carbon number of the saturated or unsaturated aliphatic hydrocarbon group is preferably 1 to 100, more preferably 2 to 50, and further preferably 4 to 40. In addition, the carbon number of the saturated or unsaturated aliphatic hydrocarbon group may be 8 to 100, 8 to 50, 15 to 50, 25 to 50, or 30 to 45. The saturated or unsaturated aliphatic hydrocarbon group may be any one of a straight chain group, a branched chain group, and a cyclic group, or a combination thereof. As the cyclic group, an alicyclic hydrocarbon group is preferred. As the saturated or unsaturated aliphatic hydrocarbon group, a combination of a straight chain group and a cyclic group is preferred, and a combination of a straight chain group and an alicyclic hydrocarbon group is more preferred.

[0086] [Chemistry 1]

[0087]

[0088] [Chemistry 2]

[0089]

[0090] In the above general formula (1) and general formula (2), x represents an integer of 10 to 50, preferably an integer of 20 to 40. In the above general formula (2), n represents the number of structural units surrounded by bond brackets, and is preferably an integer of 0 to 50, more preferably an integer of 1 to 30, further preferably an integer of 1 to 20, and particularly preferably an integer of 1 to 10.

[0091] Specific examples of the maleimide compound represented by the general formula (2) include compounds represented by the following formula (3). In the following formula (3), n represents the number of structural units enclosed in parentheses and represents an integer of 1 to 10.

[0092] [Chemistry 3]

[0093]

[0094] The number average molecular weight (Mn) of the maleimide elastomer is the same as the number average molecular weight (Mn) of the component (A1), and is preferably 10,000 or more and less than 100,000, and may be 10,000 to 50,000, 15,000 to 35,000, or 17,000 to 30,000.

[0095] ((A2) Elastomer having a number average molecular weight of less than 10,000)

[0096] The component (A) may contain an elastomer other than the "elastomer (A1) having a number average molecular weight of 10,000 or more", that is, "elastomer (A2) having a number average molecular weight of less than 10,000", or may not contain it, but preferably contains it. The component (A2) has the effect of improving the compatibility of the component (A1) with the "(A3) thermosetting resin" described later.

[0097] From the viewpoint of improving the compatibility of the component (A1) with the "(A3) thermosetting resin" described later, the number average molecular weight (Mn) of the component (A2) is preferably 300 or more and less than 10,000, more preferably 400 to 9,000, and may be 500 to 6,000, 1,000 to 5,500, 1,500 to 5,000, 2,000 to 5,000, or 2,500 to 4,000.

[0098] Component (A2) includes the same substances as component (A1), wherein, from the viewpoint of improving the compatibility of component (A1) with the "(A3) thermosetting resin" described later, and from the viewpoint of relative dielectric constant (Dk) and dielectric loss tangent (Df), at least one selected from polybutadiene elastomers and styrene elastomers is preferred, and it may be a polybutadiene elastomer or a styrene elastomer.

[0099] (Polybutadiene elastomer; component (A2))

[0100] Examples of the polybutadiene elastomer include polybutadiene diol, polybutadiene dicarboxylic acid, maleated polybutadiene, butadiene homopolymer, copolymers copolymerizable with butadiene, compounds obtained by reacting polybutadiene diol with a compound having an isocyanate group, compounds obtained by reacting polybutadiene diol with a compound having a carboxyl group, compounds obtained by reacting polybutadiene dicarboxylic acid with a compound having a hydroxyl group, compounds obtained by reacting polybutadiene dicarboxylic acid with a compound having an epoxy group, etc. Among them, butadiene homopolymer is preferred as the polybutadiene elastomer.

[0101] The number average molecular weight (Mn) of the polybutadiene-based elastomer used as the component (A2) is as described above with respect to the number average molecular weight (Mn) of the component (A2).

[0102] As the polybutadiene-based elastomer, a commercially available product can be used.

[0103] Examples of commercially available products of the polybutadiene dicarboxylic acid include C-1000 (1,2-structural unit content: 85% or more, manufactured by Nippon Soda Co., Ltd., trade name).

[0104] Commercially available products of the butadiene homopolymer include B-1000 (1,2-structural unit content: 85%), B-2000 (1,2-structural unit content: 85%), and B-3000 (1,2-structural unit content: 90%) (these are trade names, manufactured by Nippon Soda Co., Ltd.).

[0105] Examples of commercially available products of the compound obtained by reacting the polybutadiene diol with a compound having an isocyanate group include TEAI-1000 and TE-2000 (trade names, manufactured by Nippon Soda Co., Ltd.).

[0106] Examples of commercially available products of the compound obtained by reacting the polybutadiene dicarboxylic acid with a compound having an epoxy group include EPB13 (trade name, manufactured by Nippon Soda Co., Ltd.).

[0107] (Styrene elastomer; component (A2))

[0108] Examples of the styrene elastomer include the same ones as those in the component (A1). The number average molecular weight (Mn) of the styrene elastomer used as the component (A2) is as described above for the number average molecular weight (Mn) of the component (A2).

[0109] As the styrene-based elastomer, a commercially available product may be used.

[0110] (Total content of component (A1) and component (A2))

[0111] The total content of the (A1) component and the (A2) component is preferably 40 to 95% by mass, more preferably 45 to 95% by mass, further preferably 50 to 90% by mass, and can also be 55 to 90% by mass, and can be 65 to 85% by mass. The total content of the (A1) component and the (A2) component is above the lower limit, so that the main component of the resin sheet is an elastomer, the dielectric loss tangent (Df) is reduced, and there is a tendency for the resin sheet to have high flexibility. The total content of the (A1) component and the (A2) component is below the upper limit, so that the (A3) thermosetting resin described later can be fully contained, so that it is easy to give the resin sheet various characteristics such as low thermal expansion, heat resistance and adhesion to the conductor.

[0112] ((A3) Thermosetting resin)

[0113] The component (A) may further contain a thermosetting resin as the component (A3). The inclusion of a thermosetting resin can improve the heat resistance of the resin sheet. The component (A3) may be used alone or in combination of two or more.

[0114] As thermosetting resin, epoxy resin, phenolic resin, unsaturated imide resin, cyanate resin, isocyanate resin, benzoxazine resin, oxetane resin, amino resin, unsaturated polyester resin, allyl resin, vinyl benzyl resin, dicyclopentadiene resin, silicone resin, triazine resin, modified polyphenylene ether resin, melamine resin etc. can be enumerated, preferably contain more than one selected from them.In addition, it is not particularly limited to these, and known thermosetting resin can also be used.Wherein, from the viewpoint of low thermal expansion and heat resistance and with the viewpoint of adhesion of conductor, unsaturated imide resin, vinyl benzyl resin are preferably used.It should be noted that the modified polyphenylene ether resin is a polyphenylene ether resin with reactive groups such as vinyl and (methyl) acrylic acid.

[0115] As the unsaturated imide resin, from the viewpoint of low thermal expansion and heat resistance, and the viewpoint of adhesion to the conductor, a maleimide compound is preferred. As the maleimide compound, one or more selected from maleimide compounds having one or more N-substituted maleimide groups and their derivatives can be cited. It should be noted that the maleimide compound mentioned here does not include the maleimide-based elastomer.

[0116] The maleimide compound having one or more N-substituted maleimide groups is preferably a maleimide compound having two or more N-substituted maleimide groups. In the maleimide compound having two or more N-substituted maleimide groups, the nitrogen atoms of the two or more maleimide groups are preferably bonded via an organic group.

[0117] Examples of the “derivative of a maleimide compound having one or more N-substituted maleimide groups” include addition reaction products of the maleimide compound having one or more N-substituted maleimide groups and an amine compound such as a diamine compound.

[0118] As the maleimide compound, from the viewpoint of low thermal expansion and heat resistance, and the viewpoint of adhesion to the conductor,

[0119] Preferably, it is selected from maleimide compounds having one or more N-substituted maleimide groups, and

[0120] Aminomaleimide compound having a structural unit derived from a maleimide compound and a structural unit derived from a diamine compound

[0121] One or more of the following.

[0122] The vinylbenzyl resin is not particularly limited as long as it is a compound having a vinylbenzyl group, but preferably contains one or more selected from compounds having three or more vinylbenzyl groups bonded to oxygen atoms and compounds having one or more vinylbenzyl groups bonded to carbon atoms. In addition, from the viewpoint of dielectric properties, the vinylbenzyl resin is preferably a vinylbenzyl resin containing one or more rings selected from fluorene rings and indene rings. The vinylbenzyl group may be any one of o-vinylbenzyl, m-vinylbenzyl or p-vinylbenzyl.

[0123] When the component (A) further contains a thermosetting resin (A3), the content of the component (A3) is not particularly limited, and is preferably 5 to 60% by mass, more preferably 5 to 55% by mass, further preferably 10 to 50% by mass, 10 to 45% by mass, or 15 to 35% by mass, based on the component (A). When the content of the component (A3) is above the lower limit, it is easy to impart various properties such as low thermal expansion, heat resistance, and adhesion to a conductor to the resin sheet, and when it is below the upper limit, the main component of the resin sheet is an elastomer, the dielectric loss tangent (Df) is reduced, and there is a tendency that the resin sheet has high flexibility.

[0124] The total content of the components (A1), (A2) and (A3) in the component (A) is preferably 50 to 100% by mass, more preferably 80 to 100% by mass, further preferably 90 to 100% by mass, particularly preferably 95 to 100% by mass, and may be 100% by mass.

[0125] The content of the component (A) is not particularly limited, but is preferably 80 to 100% by mass, more preferably 85 to 100% by mass, further preferably 90 to 100% by mass, and particularly preferably 95 to 100% by mass based on the total amount of the resin components in the resin sheet.

[0126] ((B) Inorganic filler)

[0127] The resin sheet of this embodiment contains an inorganic filler as a component (B), and the content of the component (B) is 25 to 70% by volume based on the total amount of the resin sheet. By containing 25% by volume or more of the component (B), the low thermal expansion property is improved while reducing the viscosity of the resin sheet, making it easy to peel the resin sheet from the support. By having a content of the component (B) of 70% by volume or less, it is easy to control the fracture energy of the resin sheet to the specified value. The component (B) can be used alone or in combination of two or more.

[0128] As the inorganic filler, there is no particular limitation, and silicon dioxide, aluminum oxide, titanium oxide, mica, beryllium oxide, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay (burned clay, etc.), molybdate compounds such as zinc molybdate, talc, aluminum borate, silicon carbide, etc. can be cited. They can be used alone or in combination of more than two. Among these, from the viewpoint of thermal expansion coefficient, elastic modulus, heat resistance and flame retardancy, preferably silicon dioxide, aluminum oxide, mica, molybdate compounds, talc, more preferably silicon dioxide, aluminum oxide, further preferably silicon dioxide. Examples of silica include precipitated silica with a high water content produced by a wet process, and dry-process silica containing almost no bound water produced by a dry process. Dry-process silica also includes crushed silica, fumed silica, and fused silica (fused spherical silica), depending on the production method.

[0129] The shape of the inorganic filler is not particularly limited, and may be spherical, needle-like, flaky, plate-like, or the like. From the viewpoint of facilitating high filling of the inorganic filler, a spherical shape is preferred.

[0130] Among them, in this embodiment, (B) inorganic filler does not include fiber substrates such as glass cloth, and further, does not include glass fibers. Therefore, in the case where the resin sheet of this embodiment contains fiber substrates such as glass cloth or glass fibers, it is not contained as (B) component but as other components, and the content of fiber substrate or glass fibers is preferably within the above range (i.e., 10% by volume or less, preferably 7% by volume or less, more preferably 5% by volume or less, and further preferably 3% by volume or less based on the total amount of the resin sheet), and the total content of fiber substrate and glass fibers is preferably 10% by volume or less, more preferably 7% by volume or less, further preferably 5% by volume or less, and particularly preferably 3% by volume or less based on the total amount of the resin sheet.

[0131] The inorganic filler may not be surface-treated with a coupling agent, but may be surface-treated with a coupling agent such as a silane coupling agent from the viewpoint of improving dispersibility in the resin sheet, and is preferably surface-treated with a coupling agent such as a silane coupling agent.

[0132] Examples of the silane coupling agent include aminosilane coupling agents, epoxysilane coupling agents, phenylsilane coupling agents, alkylsilane coupling agents, alkenylsilane coupling agents, alkynylsilane coupling agents, haloalkylsilane coupling agents, siloxane coupling agents, hydrogensilane coupling agents, silazane coupling agents, alkoxysilane coupling agents, chlorosilane coupling agents, (meth)acrylic silane coupling agents, isocyanurate silane coupling agents, urea silane coupling agents, mercaptosilane coupling agents, sulfide silane coupling agents, isocyanate silane coupling agents, etc. Among them, aminosilane coupling agents, alkenylsilane coupling agents, and (meth)acrylic silane coupling agents are preferred.

[0133] The average particle size of the inorganic filler is not particularly limited, but is preferably 0.01 to 20 μm, more preferably 0.1 to 10 μm, further preferably 0.2 to 8 μm, particularly preferably 0.3 to 5 μm, and may be 0.5 to 5 μm, 0.5 to 3 μm, or 0.5 to 1.5 μm.

[0134] As the inorganic filler, a plurality of types having different average particle sizes may be used in combination. By using a plurality of types having different average particle sizes in combination, there is a tendency that the resin sheet is easily filled with a high amount of the inorganic filler.

[0135] Here, in this specification, the average particle size is: the particle size corresponding to the point of 50% volume when the cumulative number distribution curve based on the particle size is obtained with the total volume of the particles as 100%. The particle size of the inorganic filler can be measured by a particle size distribution measuring device using a laser diffraction scattering method, and the same is true below.

[0136] The content of the component (B) is as described above, and is 25 to 70% by volume, preferably 30 to 70% by volume, more preferably 35 to 70% by volume, further preferably 45 to 70% by volume, particularly preferably 50 to 70% by volume, and may be 50 to 65% by volume, based on the total amount of the resin sheet. When the content of the component (B) is above the lower limit, the low thermal expansion is excellent, and the viscosity of the resin sheet is sufficiently reduced. When the content of the component (B) is below the upper limit, the industrial transportability is excellent.

[0137] In this way, since the feature A can be present in the present embodiment, it is possible to achieve a high filling (B) component in the resin sheet. It should be noted that, in the case of a prepreg instead of a resin sheet such as the present embodiment, since the feature A is not present, 55% by volume is the actual upper limit for the content of the inorganic filler based on the total amount of the resin composition in the prepreg. If the prepreg contains more than 55% by volume of the inorganic filler, the inorganic filler will overflow due to the presence of the fiber substrate, so the melting of the resin composition will become difficult, and as a result, there will be a tendency to be unable to make the prepreg.

[0138] ((C) Organic filling material)

[0139] The resin sheet of the present embodiment may or may not contain an organic filler as component (C). The resin sheet of the present embodiment contains an organic filler, which tends to further reduce the dielectric loss tangent (Df) and to adjust the relative dielectric constant (Dk) to the specified range.

[0140] There is no particular limitation on the organic filler material, and examples thereof include: resin particles of a single structure comprising polyethylene, polypropylene, polystyrene, polyphenylene ether resin, silicone resin or tetrafluoroethylene resin; resin particles of a core-shell structure having a rubbery core layer comprising an acrylate resin, methacrylate resin or conjugated diene resin, and a glassy shell layer comprising an acrylate resin, methacrylate resin, aromatic vinyl resin or cyanide vinyl resin, etc.; and the like.

[0141] The average particle size of the organic filler is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm, further preferably 0.5 to 4.0 μm, and particularly preferably 1.5 to 4.0 μm.

[0142] When the resin sheet of the present embodiment contains (C) an organic filler, the content thereof is not particularly limited, but is preferably 1 to 30% by volume, more preferably 3 to 25% by volume, and even more preferably 5 to 20% by volume based on the total volume of the resin sheet.

[0143] ((D) Thermal polymerization initiator)

[0144] The resin sheet of the present embodiment may further contain a thermal polymerization initiator as the component (D).

[0145] The thermal polymerization initiator is not particularly limited, and examples thereof include hydroperoxide compounds such as diisopropylbenzene hydroperoxide "PERCUMYL P" (trade name, manufactured by NOF Corporation (hereinafter the same)), cumene hydroperoxide "PERCUMYL H", and tert-butyl hydroperoxide "PERBUTYL H"; α,α-bis(tert-butylperoxy-m-isopropyl)benzene "PERBUTYL P", diisopropylbenzene peroxide "PERCUMYL D", 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane "PERHEXA 25B", tert-butylcumene peroxide "PERBUTYL C", di-tert-butyl peroxide "PERBUTYL D", 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3 "PERHEXYNE 25B", tert-butyl peroxy-2-ethylhexanoate "PERBUTYL O" and other dialkyl peroxide compounds; ketone peroxide compounds; peroxyketal compounds such as n-butyl 4,4-di(tert-butylperoxy)valerate "PERHEXA V"; diacyl peroxide compounds; peroxydicarbonate compounds; organic peroxides such as peroxyester compounds; azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), etc. Among them, α,α-bis(tert-butylperoxy-m-isopropyl)benzene "PERBUTYL P" is preferred.

[0146] When the resin sheet of the present embodiment contains (D) a thermal polymerization initiator, the content thereof is not particularly limited, but is preferably 0.01 to 5% by mass, more preferably 0.1 to 4% by mass, and further preferably 0.5 to 3% by mass, based on the component (A). When the content of the thermal polymerization initiator (D) is above the lower limit, a sufficiently thermally cured resin sheet tends to be easily obtained, and when it is below the upper limit, heat resistance tends to be good.

[0147] (Other ingredients)

[0148] The resin sheet of the present embodiment may also contain other components. There are no particular restrictions on other components, and examples thereof include curing accelerators, flame retardants, flame retardant aids, peroxides, antioxidants, fluorescent brighteners, adhesion improvers, heat stabilizers, antistatic agents, ultraviolet absorbers, pigments, colorants, lubricants, and the like.

[0149] When the resin sheet of the present embodiment contains other components, the content of each component is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, and may be 0.1% by mass or more, or 0.5% by mass or more, based on the total amount of the resin sheet.

[0150] (Thickness of resin sheet)

[0151] The thickness of the resin sheet of the present embodiment is preferably the same as the thickness of one prepreg used for printed wiring board applications in the past, and may be preferably 10 to 120 μm, more preferably 20 to 110 μm, further preferably 20 to 100 μm, or 40 to 100 μm, or 60 to 100 μm. However, the thickness of the resin sheet of the present embodiment is not limited to the above range.

[0152] (Method for producing resin sheet)

[0153] The resin sheet of the present embodiment can be manufactured, for example, by applying a resin composition mixed with the above-mentioned components and an organic solvent as required to a support, heating and drying it to B-stage it, and then peeling off the support. Here, in this specification, B-stage means: becoming a state of the first stage B defined in JIS K6900 (1994), also known as semi-curing.

[0154] Examples of the support include films of polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; films of polyesters such as polyethylene terephthalate (hereinafter also referred to as "PET") and polyethylene naphthalate; various plastic films such as polycarbonate films and polyimide films; metal foils such as copper foil and aluminum foil; and release paper. The support may be subjected to a surface treatment such as a matte treatment and a corona treatment. In addition, the support may be subjected to a release treatment using a silicone resin release agent, an alkyd resin release agent, a fluororesin release agent, or the like.

[0155] The thickness of the support is not particularly limited, but is preferably 10 to 150 μm, more preferably 25 to 80 μm.

[0156] The method for coating the resin composition on the support is not particularly limited, and coating can be performed using coating devices known to those skilled in the art such as a comma coater, a rod coater, a kiss coater, a roll coater, a gravure coater, a die coater, etc. These coating devices can be appropriately selected according to the thickness of the resin sheet to be manufactured.

[0157] The drying temperature and drying time after coating the resin composition are not particularly limited, and examples thereof include a method of drying at 50 to 140° C. for about 3 to 15 minutes. The drying temperature is preferably 70 to 135° C., more preferably 80 to 130° C. The drying time is preferably 3 to 12 minutes.

[0158] The resin sheet of this embodiment may also be provided with a protective film on one or both sides. By providing a protective film, it is possible to avoid damage during transportation. In addition, the resin sheet of this embodiment may not be provided with a protective film.

[0159] [Laminated plate, metal-clad laminated plate]

[0160] The laminated plate of the present embodiment is a laminated plate containing a cured product of the resin sheet of the present embodiment. The laminated plate having a metal foil is sometimes referred to as a metal-clad laminated plate, that is, the metal-clad laminated plate of the present embodiment is a metal-clad laminated plate containing a metal foil and a cured product of the resin sheet of the present embodiment.

[0161] The metal-clad laminate of the present embodiment can be manufactured, for example, by configuring metal foil on one or both sides of a resin sheet of the present embodiment, or configuring metal foil on one or both sides of a laminated sheet obtained by overlapping two or more (preferably 2 to 20 sheets, more preferably 2 to 10 sheets) of the resin sheets of the present embodiment, and then heating and pressurizing the laminated sheet.

[0162] As another method for manufacturing a metal-clad laminate of the present embodiment, the following method can be cited: a resin film other than the present embodiment is configured with a metal foil after configuring one or more resin films other than the present embodiment on one or both sides of a resin sheet of the present embodiment, and a method of heating and pressing. In this case, when using more than two resin films other than the present embodiment, each can be the same resin film, or different resin films can be combined. The same resin film refers to a resin film with the same composition, and different resin films refer to resin films with different compositions, which are the same below. Here, as the resin film other than the present embodiment, a known resin film with a support for multilayering of a printed wiring board can be used, which is the same below.

[0163] As another method for manufacturing a metal-clad laminate of the present embodiment, there can be cited a method of: placing one or more resin films other than the present embodiment on one or both sides of a laminate obtained by stacking two or more (preferably 2 to 20, more preferably 2 to 10) resin sheets of the present embodiment, and then placing metal foil, and heating and pressing. In this case, when two or more resin films other than the present embodiment are used, each may be the same resin film, or different resin films may be combined.

[0164] The metal of the metal foil is not particularly limited as long as it can be used as an electrical insulating material. From the perspective of conductivity, it can be copper, gold, silver, nickel, platinum, molybdenum, ruthenium, aluminum, tungsten, iron, titanium, chromium, or an alloy containing one or more of these metal elements, preferably copper and aluminum, and more preferably copper.

[0165] The conditions for heat press molding are not particularly limited, and for example, it can be carried out under the following conditions: the temperature is preferably 100 to 300° C., more preferably 150 to 250° C., and further preferably 180 to 240° C., the pressure is preferably 0.2 to 10 MPa, more preferably 1.5 to 6 MPa, and the time is preferably 0.1 to 5 hours, and more preferably 1 to 3 hours. In addition, heat press molding can be carried out by a method of maintaining a vacuum state for preferably 0.5 to 5 hours using a vacuum press or the like.

[0166] It should be noted that in the laminated plate and the metal-clad laminated plate of the present embodiment, the resin sheet is C-staged to become a cured product. That is, the laminated plate of the present embodiment contains the C-staged resin sheet, and it can also be said that the metal-clad laminated plate of the present embodiment contains the C-staged resin sheet and metal foil.

[0167] Here, in this specification, C-stage means a state of being in the C-stage defined in JIS K6900 (1994).

[0168] [Printed circuit board]

[0169] The printed wiring board of the present embodiment contains the laminated board or metal-clad laminated board of the present embodiment. Here, the expression "containing the laminated board or metal-clad laminated board" includes the following two cases: the case where the laminated board or metal-clad laminated board is directly contained; and the case where the laminated board or metal-clad laminated board is contained in a state where a hole-forming process, metal plating process, circuit forming process using etching of metal foil, etc., is performed on the laminated board or metal-clad laminated board.

[0170] The printed wiring board of this embodiment can be manufactured by the following method: using a laminate of this embodiment having a metal foil on one or both sides, i.e., a metal-clad laminate, performing hole opening processing, metal plating processing, circuit forming processing using etching of the metal foil, etc. by a known method, and further performing multilayer processing as needed.

[0171] [Semiconductor package]

[0172] The semiconductor package of this embodiment is a semiconductor package including the printed wiring board of this embodiment and a semiconductor element. The semiconductor package of this embodiment can be manufactured by mounting semiconductor elements such as semiconductor chips and memories at predetermined positions of the printed wiring board of this embodiment and sealing the semiconductor elements with a sealing resin or the like.

[0173] The resin sheet, laminate, printed wiring board, and semiconductor package of the present embodiment can be suitably used in electronic devices that process high-frequency signals of 10 GHz or higher. In particular, the printed wiring board is useful as a printed wiring board for millimeter wave radar.

[0174] The preferred embodiments are described above, but this is for illustration of the present application and is not intended to limit the scope of the present application to these embodiments. The present application may be implemented in various ways different from the above embodiments without departing from the gist of the present application.

[0175] Example

[0176] The present embodiment will be described in detail below with reference to examples, but the present embodiment is not limited to the following examples.

[0177] Preparation Example 1: Preparation of Vinylbenzyl Resin

[0178] In a 500 mL reaction container equipped with a stirring device, a thermometer, a reflux tube and a nitrogen gas blowing port, 35.6 parts by mass of indene, 101.2 parts by mass of chloromethylstyrene (a mixture of 50% by mass of meta-isomer and 50% by mass of para-isomer), 7.1 parts by mass of tetra-n-butylammonium bromide (phase transfer catalyst), 0.1 parts by mass of phenothiazine (polymerization inhibitor) and 77.6 parts by mass of toluene (solvent) were charged, and the mixture was heated and stirred at 40° C. while nitrogen gas was blown in at a flow rate of 50 ml / min.

[0179] Next, 46.5 parts by weight of a 48% by weight aqueous sodium hydroxide solution was added dropwise over 20 minutes, and the mixture was stirred at 60° C. for 9 hours. It should be noted that nitrogen was continuously blown in during the reaction. The mixture was cooled to room temperature (25° C.) and neutralized with a 10% aqueous hydrochloric acid solution, and then washed twice with pure water. After toluene was removed by vacuum distillation, the obtained viscous liquid was washed with methanol and then vacuum dried to obtain vinyl benzyl resin A3-1.

[0180] pass 1 H-NMR analysis confirmed that the vinylbenzyl resin A3-1 had a structure in which substantially all of the two hydrogen atoms directly bonded to the carbon atom at position 1 of the indene represented by the following formula (A3-1) were substituted by vinylbenzyl groups. In addition, GPC analysis showed that the vinylbenzyl resin A3-1 was a mixture of a resin having two vinylbenzyl groups introduced and a resin having three vinylbenzyl groups introduced.

[0181] [Chemistry 4]

[0182]

[0183] Examples 1 to 10, Comparative Examples 1 to 4

[0184] (Production of resin sheets)

[0185] Each component described in Table 1 or Table 2 was stirred and mixed with toluene at room temperature (25° C.) in the blending amounts described in Table 1 or Table 2 to prepare a resin composition having a solid content concentration of 60% by mass.

[0186] The prepared resin composition was applied to a PET film (manufactured by Toyobo Co., Ltd., trade name: Purex (registered trademark) A5300) having a thickness of 50 μm, and then heated and dried at 110° C. for 5 minutes to make the resin composition B one-stage, and as a result, a resin sheet with a PET film (width 500 mm×length 500 mm, thickness 80 μm) was obtained. For the resin sheet with a PET film, one corner of the PET film was grasped with tweezers, and the PET film was slowly peeled off from the resin sheet toward the other corner on the diagonal line to obtain an exposed resin sheet.

[0187] (Manufacturing of copper-clad laminates)

[0188] The resin sheets obtained by the above method are overlapped by 4 or 10 sheets to form a laminate. On the upper and lower sides of the laminate, a low-profile copper foil (Mitsui Mining and Smelting Co., Ltd., trade name: SI VSP AM 3R) with a thickness of 18 μm is arranged in a state where its M surface (rough surface) is in contact with the laminate, and is heated and pressed under the conditions of a temperature of 230° C., a pressure of 2 MPa, and a time of 120 minutes, thereby making the resin sheet C a stage, thereby making a two-sided copper-clad laminate (a two-sided copper-clad laminate using 4 resin sheets is referred to as "two-sided copper-clad laminate A", and a two-sided copper-clad laminate using 10 resin sheets is referred to as "two-sided copper-clad laminate B").

[0189] [Evaluation and measurement methods]

[0190] The resin sheets or copper-clad laminates obtained in the above Examples and Comparative Examples were used to perform various measurements and evaluations according to the following methods.

[0191] (1. Evaluation of industrial transportability)

[0192] The resin sheet peeled off from the PET film in each example was adsorbed by a vacuum adsorption pad (diameter 20 mm, made of silicone) using an adsorption machine, and then transported 500 mm in the horizontal direction. It should be noted that the vacuum degree during transport and adsorption was -27 kPa. The situation at this time was evaluated according to the following evaluation criteria as an indicator of industrial transportability.

[0193] Evaluation A means that the industrial transportability is excellent, evaluation B means that the resin sheet can be self-supporting without a support but the industrial transportability is insufficient, and evaluation C means that the resin sheet cannot even be self-supporting.

[0194] A: The resin sheet was not damaged even after being transported by the vacuum pad.

[0195] B: The resin sheet was damaged when it was adsorbed by the vacuum adsorption pad or during transportation.

[0196] C: The resin sheet was damaged when the PET film was peeled off.

[0197] (2. Determination of fracture energy)

[0198] Five evaluation resin sheets (width 10 mm × length 40 mm) were prepared from the resin sheets peeled from the PET film in each example, and a tensile test was performed in the longitudinal direction using an automatic plotter (AG-X, manufactured by Shimadzu Corporation). Each evaluation resin sheet was measured under the conditions of a measurement temperature of 25°C, a distance between chucks of 20 mm, and a tensile speed of 10 mm / min.

[0199] It should be noted that the fracture energy is calculated by integrating the stress from the starting point of the stretching (initial chuck distance) to the fracture point of each test piece (displacement when the test piece breaks) with displacement. The obtained fracture energy is divided by the volume of the test piece to obtain the fracture energy per unit volume (mJ / mm 3 ). The average value of 5 measurements was taken as the breaking energy of the resin sheet.

[0200] (3. Determination of fracture vacuum)

[0201] For the resin sheet peeled off from the PET film in each example, a suction machine equipped with a vacuum suction pad (20 mm in diameter, made of silicone) was used. After setting the vacuum degree to an arbitrary value, the vacuum suction pad was used to suction for 3 seconds, and then the vacuum was released to normal pressure to visually check whether the resin sheet was broken. If the resin sheet was not broken, a higher vacuum degree was set again, and the same operation was performed at a different location from the previous one. When the resin sheet was broken at the suction part (refer to Figure 1 ) is taken as the fracture vacuum degree.

[0202] When the breaking vacuum degree is -15 kPa or less (preferably -20 kPa or less, more preferably -30 kPa or less, and further preferably -40 kPa or less), it is preferable because adsorption and transportation using a vacuum adsorption pad for transportation can be easily performed.

[0203] (4. Dielectric properties; determination of relative dielectric constant and dielectric loss tangent)

[0204] An evaluation substrate of 40 mm×50 mm was prepared from the double-sided copper-clad laminate A obtained in each example by immersing the double-sided copper-clad laminate A in a 10 mass % solution of ammonium persulfate (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a copper etching solution to remove the copper foil.

[0205] Using this evaluation substrate, relative dielectric constant and dielectric loss tangent were measured at 25° C. in a 10 GHz frequency band using “PNA Network Analyzer N5227A” (manufactured by Agilent Technologies) equipped with a separated dielectric resonator (SPDR).

[0206] (5. Determination of thermal expansion coefficient)

[0207] The double-sided copper-clad laminate B obtained in each example was immersed in a copper etching solution to prepare a 5 mm square evaluation substrate from which the copper foil was removed, and thermomechanical analysis was performed by a compression method using a thermomechanical analyzer (TMA) [manufactured by TA Instruments Japan, Q400 (model)].

[0208] After the evaluation substrate was mounted on the device along the X direction, it was continuously measured twice under the measurement conditions of a load of 5 g and a heating rate of 10°C / min. The average thermal expansion coefficient (average of the linear thermal expansion coefficient in the plane direction) from 50°C to 120°C in the second measurement was calculated and used as the value of the thermal expansion coefficient (linear thermal expansion coefficient). In this measurement, the second measurement result was used to improve accuracy.

[0209] (6. Determination of glass transition temperature (Tg))

[0210] The double-sided copper-clad laminate B obtained in each example was immersed in a copper etching solution to remove the copper foil. Using the 5 mm square test piece thus obtained, the glass transition temperature was measured using a thermomechanical measurement apparatus (TMA) [manufactured by TA Instruments Japan Co., Ltd., Q400 (model)] based on the IPC (The Institute for Interconnecting and Packaging Electronic Circuits) standard.

[0211] The higher the glass transition temperature, the more excellent the heat resistance.

[0212] [Table 1]

[0213] Table 1

[0214]

[0215] *1: Phosphorus atom equivalent amount per 100 parts by mass of component (A)

[0216] [Table 2]

[0217] Table 2

[0218]

[0219] *1: Phosphorus atom equivalent amount per 100 parts by mass of component (A)

[0220] In addition, each component described in Table 1 or Table 2 is as follows.

[0221] [(A) ingredient]

[0222] ((A1) ingredient)

[0223] Elastomer 1: styrene-ethylene-butylene-styrene copolymer (SEBS), styrene content 20% by mass, hydrogenation rate 100 mol%, Mn = 70,000

[0224] ((A2) ingredient)

[0225] .Elastomer 2: 1,2-polybutadiene homopolymer, Mn=1,200

[0226] Elastomer 3: 1,2-polybutadiene homopolymer, Mn=3,200

[0227] ((A3) ingredient)

[0228] Vinylbenzyl resin: Vinylbenzyl resin A3-1 obtained in Preparation Example 1

[0229] . Unsaturated imide resin: an aromatic bismaleimide compound containing an indane ring having the following structure

[0230] [Chemistry 5]

[0231]

[0232] (In the above formula, n3 is a number between 0.95 and 10.0.)

[0233] [(B) ingredient]

[0234] ·Silica: Silica with an average particle size of 1.0μμm treated with an aminosilane coupling agent

[0235] [(D) ingredient]

[0236] Thermal polymerization initiator 1: α,α-bis(tert-butylperoxy-m-isopropyl)benzene (see the following structure)

[0237] [Chemistry 6]

[0238]

[0239] [Other ingredients]

[0240] Flame retardant 1: 1,3-phenylene bis(di-2,6-ditolyl phosphate), phosphorus content 9 mass%

[0241] In addition, the number average molecular weight of the said (A) component is measured by the following method.

[0242] (Method for measuring number average molecular weight (Mn))

[0243] The number average molecular weight is calculated by gel permeation chromatography (GPC) from a calibration curve using standard polystyrene. The standard curve uses standard polystyrene: TSKstandard POLYSTYRENE (models; A-2500, A-5000, F-1, F-2, F-4, F-10, F-20, F-40) [ToSoh Co., Ltd., trade name] and is approximated by a cubic equation. The measurement conditions of GPC are as follows.

[0244] [GPC measurement conditions]

[0245] Device: High-speed GPC device HLC-8320GPC

[0246] Detector: Ultraviolet absorption detector UV-8320 [manufactured by ToSoh Corporation]

[0247] Column: Guard column; TSK Guardcolumn SuperHZ-L + column; TSKgel SuperHZM-N + TSKgelSuperHZM-M + TSKgel SuperH-RC (all manufactured by ToSoh Co., Ltd., trade name)

[0248] Column size: 4.6×20mm (guard column), 4.6×150mm (column), 6.0×150mm (reference column)

[0249] Eluent: Tetrahydrofuran

[0250] Sample concentration: 10mg / 5mL

[0251] Injection volume: 25 μL

[0252] Flow rate: 1.00mL / min

[0253] Measurement temperature: 25℃

[0254] From the results shown in Tables 1 and 2, it can be seen that the resin sheets prepared in the examples satisfy the following requirements: (1) being able to withstand adsorption and transportation by a vacuum adsorption pad for transportation, (2) having low thermal expansion, (3) having a relative dielectric constant (Dk) in the high frequency band above 10 GHz in the range of 2.50 to 3.30, and (4) having a dielectric loss tangent (Df) of 0.0020 or less in the high frequency band above 10 GHz. It can also be seen that the resin sheets prepared in the examples have a breaking vacuum degree of -15 kPa or less, are easy to be adsorbed and transported by a vacuum adsorption pad for transportation, and have good heat resistance.

[0255] On the other hand, the fracture energy is less than 0.1 mJ / mm 3The resin sheets of Comparative Examples 1 to 3 were not even self-supporting and were extremely poor in industrial transportability. In addition, even in Comparative Example 4, in which the resin sheet was easily self-supporting by increasing the content of component (A1), the fracture energy was small due to the high content of silica of 72 mass %, resulting in insufficient industrial transportability.

Claims

1. A resin sheet comprising (A) a resin component and (B) an inorganic filler, in, The component (A) contains (A1) an elastomer having a number average molecular weight of 10,000 or more, The content of the component (B) is 25 volume % to 70 volume % based on the total amount of the resin sheet. The fracture energy of the resin sheet is 0.1 mJ / mm 3 above.

2. The resin sheet according to claim 1, in, The component (A1) contains one or more selected from styrene elastomers, maleimide elastomers, olefin elastomers, urethane elastomers, polyester elastomers, polyamide elastomers, acrylic elastomers, silicone elastomers and derivatives thereof. 3 . The resin sheet according to claim 1 , further comprising (A2) an elastomer having a number average molecular weight of less than 10,000.

4. The resin sheet according to claim 1, in, The component (A) further contains (A3) a thermosetting resin.

5. The resin sheet according to claim 4, in, The component (A3) contains one or more selected from epoxy resins, phenolic resins, unsaturated imide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, vinylbenzyl resins, dicyclopentadiene resins, silicone resins, triazine resins, modified polyphenylene ether resins and melamine resins.

6. The resin sheet according to claim 4, in, The total content of the component (A1) and the component (A2) is 40% by mass to 95% by mass based on the component (A). 7 . The resin sheet according to claim 1 , which contains no organic solvent, or even if it contains an organic solvent, the content of the organic solvent is less than 1% by mass based on the total amount of the resin sheet. 8 . The resin sheet according to claim 1 , which does not contain glass fibers, or even if it contains glass fibers, the content of the glass fibers is 10% by volume or less based on the total amount of the resin sheet.

9. The resin sheet according to claim 1, in, When adsorbed by a silicone vacuum pad with a diameter of 20 mm, the vacuum degree at break is -15 kPa or less. 10 . A laminate comprising a cured product of the resin sheet according to claim 1 . 11 . A metal-clad laminate comprising a metal foil and a cured product of the resin sheet according to claim 1 . 12 . A printed wiring board comprising the laminate according to claim 10 or the metal-clad laminate according to claim 11 .

13. A semiconductor package comprising the printed wiring board according to claim 12 and a semiconductor element.

Citation Information

Patent Citations

  • Resin composition, prepreg, laminated plate, multilayer printed wiring board and semiconductor package

    JP2020169276A